Integrative and instrumental but low investment: The English learning motivation of Indonesian senior high school students - Muslim, Ahmad Bukhori; Hamied, Fuad Abdul; Sukyadi, Didi (Indonesian Journal of Applied Linguistics, 2020)
Considered important for global competitiveness like ASEAN Economic Society, the English proficiency of Indonesian students is unfortunately not satisfactory yet. This condition is, one of which, due to low teachers’ professionalism and students’ motivation for English learning. The motivation of students may become weak because they have not found ways to identify, drive and sustain it. Of the various studies on motivation and challenges in EFL practice in the Indonesian context, research specifically addressing how learners find motivation triggers synergized into project-based learning for sustainable and continuous English learning is still limited. This survey and interview study investigates the motivation of Senior High School (SHS) students in West Java province of Indonesia on English learning and how to drive their motivation through a collaborative project as mandated by the 2013 National Curriculum. Results of questionnaires, interviews and document analysis show that despite having integrative and instrumental motivation to learn English, the participating SHS students show low investment as indicated by low learning enthusiasm in the classroom and poor English performance. This low motivation is also related to some socioeconomic status such as school geographical location, classroom learning situation, and parental supports. The study recommends students’ involvement in a cooperative learning project which can direct and energize their English learning motivation so that they can have increased motivation, good English proficiency and become global citizens with high competitiveness.